DESCRIPTION OF THE OCCURRENCE OF GOUT IN THE ELDERLY IN NAMORIH VILLAGE - Susanti, Nofi; Siregar, Jelita Suryani; Ramadiah, Putri Suci; Megarani, Sheila (HEARTY, 2024)
The second most prevalent illness is gout in Indonesia after osteoarthritis, with an estimated prevalence of 1,6 to 13,6 cases per 100.000 population, and its prevalence increases with age. Among the 12.333.978 residents of North Sumatra Province, there are 1.800.0000 people who suffer from gout. The aim of the research conducted in Namorih Village, Pancur Batu District, Deli Serdang Regency, North Sumatra was to find out how food intake and lifestyle can influence the incidence of gout in the elderly. This quantitative analytical the study’s design was cross-sectional., meaning that data was collected simultaneously with a sample size of 40 people. The research results amounted to 40 respondents, with analysis of participants’ uric acid levels being in the low category, namely 23 people (57,5%) and high as 17 people (42,5%). As many as 37,5% of male respondents had elevated amounts of uric acid, and 50% of women respondents had elevated amounts of uric acid. The outcomes of this investigation indicate that as many as 42,5% of respondents had elevated amounts of uric acid, and although uric acid levels were still classified as normal, they were greater in older males than in older females.